Intellectual property rights, benefit-sharing and development of "improved traditional medicines": A new approach. (24th December 2015) - Willcox, Merlin; Diallo, Drissa; Sanogo, Rokia; Giani, Sergio; Graz, Bertrand; Falquet, Jacques; Bodeker, Gerard
Abstract: Ethnopharmacological relevance: Protection of intellectual property rights and benefit-sharing are key issues for all ethnopharmacological research. The International Society of Ethnobiology has produced helpful guidelines on access and benefit-sharing which are widely viewed as a "gold standard" but the question remains how best to apply these guidelines in practice. Difficult questions include ownership of traditional knowledge, making appropriate agreements, and how appropriately to share benefits. Materials and methods: We present the case study of the development of an "improved traditional medicine" for malaria in Mali and we report how benefit-sharing was applied in this case. Results: The knowledge about the selected plant came independently from several families and traditional healers. The IPR approach was to recognise that this traditional knowledge belongs to the people of Mali and was used for their benefit in developing a new "improved traditional medicine" (ITM). The traditional healer whose method of preparation was used, and who collaborated in clinical trials, did not request any financial reward but asked for the ITM to be named after him. The most sustainable benefit for the community was sharing the results of which preparation of which medicinal plant seemed to be the most effective for treating malaria. Attempts at providing a health centre and training a health worker for the village did not prove to be sustainable. Conclusions: Respect for intellectual property rights and benefit-sharing are possible even in a context where the knowledge is not owned by a clearly identified person or group of people. The most sustainable benefits are intangible rather than material: namely recognition, improved knowledge about which traditional treatment is the best and how to prepare and take it. Graphical abstract: